PECULIARITIES OF THERAPEUTIC ACTION OF MODERN MEDICAMENTS AT SHEEP TRICHUROSIS - Melnychuk, V. V. (Scientific Progress & Innovations, 2019)
The data of experimental research as to curative effectiveness of modern anti-helminthic preparations at sheep trichurosis invasion, registered on the territory of Ukraine are presented in the paper. 11 experimental and 1 control groups of sheep suffering from trichurosis invasion of medium intensity (from 310.00±24.49 to 420.00±48.42 eggs/g) were formed for experiments to determine the indices of therapeutic effectiveness. In all 9 preparations belonging to 4 chemical groups: benzimidazole (Brovalzene pulvis, Albendazole-250 tab-lets, and Albendazole 10 % suspension), imidothiazole (Brovalevamizole 8 % pulvis and Levavet 10 % injec-tion solution), macro-cyclic lactones (Univerm pulvis and Ivermecvet 1 % injection solution), combined preparations Combitrem emulsion and Cloziverone injection solution) were studied. The investigated medicaments were used according to the recommendations given in enclosure sheets. Powdered forms of preparations were simultaneously administered both by group method and individually in the form of treat-ment-feed mixture. It was established that all the studied medicaments had expressed nematocide properties against the causal agent of sheep trichurosis (EE from 40 to 100 % at IE from 73.33 to 100 %). It was prov-en that their effectiveness depended on the method of administering and chemical group, to which they be-longed. Injection preparation forms Levavet 10 %, Ivermecvet 1 %, and Cloziverone injected subcutaneously one time turned out to be the most effective (EE and IE 100 %). Somewhat lower indices of curative effec-tiveness (EE from 80 to 90 % at IE from 90.09 to 90.33 %) were obtained while administering Combitrem emulsion individually to diseased sheep and also Brovalevamizole 8% and Univerm pulvis also individually. Using Albendazole-250 tablets, Albendazole 10% suspension, Brovalzene pulvis by individual administra-tion and Brovalemizole 10% and Univerm pulvis by group feeding in the form of treatment-feed mixture was less effective (EE from 50 to 70 % at IE from 80.24 to 86.29 %). Group therapy of sheep using Brovalzene pulvis in treatment-feed mixture turned out to be ineffective (EE – 40 % at IE −73.33 %) at trichurosis.